O impacto do treinamento sobre avaliação multidimensional em profissionais da saúde da atenção primária de Palmas - TO - Araújo, Emily Quintana Xavier de (2021)
Introduction: Permanent Education in Health must be guided by problems of daily life and the practices of workers, in this sense, with the increase of the elderly population and, consequently, of the diseases found in aging, there is a need for trained teams to serve this population according to their particularities. For the professional to assess the needs of the elderly, one of the instruments to be used is multidimensional assessment. With this evaluation, preventive action can be taken, delaying limitations, diseases, dependence and other factors, promoting a better quality of life for the elderly. Objective: To evaluate the effect of training on multidimensional assessment of the elderly in Primary Care professionals. Methodology: This is a quasi-experimental study with a post-test that was carried out with Primary Care professionals in the city of Palmas, TO. For educational action, we used the methodological strategy of problematization through the Arco de Maguerez, following the steps: observation of reality, key points, theorization, hypothesis of solution and application to reality. The meetings were structured as conversation circles and were held over two days in the evening with a workload of three hours daily. To assess the impact of training at work and support for transference, a scale was applied 45 days after the intervention on the application of the knowledge acquired in training in their work environment. The scale contains 34 items (12 from the impact of training and 22 from support to transfer) whose responses are of the Likert type of agreement, expressed by 1 to 5 points. For the descriptive statistical evaluation, the means and standard deviations of the quantitative and percentage variables were calculated for the categorical variables. Spearman's correlation was calculated at a significance level of 5%. Results: Among the professionals evaluated, 75% were female, with an average age of 29.25 years, 37.5% reported having less than six months of training, 62.5% reported that they had no specific health discipline of the elderly and 87.5% stated they had no knowledge about multidimensional assessment of the elderly. A positive training impact was observed, whose average value was 3.84 (SD = 0.67). There was a significant correlation between the scores of the training impact scale and the support scale for material transfer (Rho = 0.74; p = 0.037). Conclusion: The data revealed a positive effect of training among primary care professionals, as well as the association between the impact of training at work and the material support for training transfer. The importance of educational actions that deal with the theme was highlighted, as well as the importance of the support offered by health institutions, especially with regard to material resources for carrying out training